Palm Tocotrienol Supplementation Enhanced Bone Formation in Oestrogen-Deficient Rats. (22nd October 2012) - Soelaiman, Ima Nirwana; Ming, Wang; Abu Bakar, Roshayati; Hashnan, Nursyahrina Atiqah; Mohd Ali, Hanif; Mohamed, Norazlina; Muhammad, Norliza; Shuid, Ahmad Nazrun
Abstract : Postmenopausal osteoporosis is the commonest cause of osteoporosis. It is associated with increased free radical activity induced by the oestrogen-deficient state. Therefore, supplementation with palm-oil-derived tocotrienols, a potent antioxidant, should be able to prevent this bone loss. Our earlier studies have shown that tocotrienol was able to prevent and even reverse osteoporosis due to various factors, including oestrogen deficiency. In this study we compared the effects of supplementation with palm tocotrienol mixture or calcium on bone biomarkers and bone formation rate in ovariectomised (oestrogen-deficient) female rats. Our results showed that palm tocotrienols significantly increased bone formation in oestrogen-deficient rats, seen by increased double-labeled surface (dLS/Bs), reduced single-labeled surface (sLS/BS), increased mineralizing surface (MS/BS), increased mineral apposition rate (MAR), and an overall increase in bone formation rate (BFR/BS). These effects were not seen in the group supplemented with calcium. However, no significant changes were seen in the serum levels of the bone biomarkers, osteocalcin, and cross-linked C-telopeptide of type I collagen, CTX. In conclusion, palm tocotrienol is more effective than calcium in preventing oestrogen-deficient bone loss. Further studies are needed to determine the potential of tocotrienol as an antiosteoporotic agent.